2011
DOI: 10.1007/s10495-011-0683-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes

Abstract: MicroRNAs (miRNAs) are a novel class of powerful, endogenous regulators of gene expression. In an intact rat model of myocardial ischemia caused by coronary artery ligation, this study identified 17 miRNAs that changed more than 1.5-fold in the myocardium subjected to 4-h ischemia. Using miRNA microarray analysis, most of these aberrantly expressed miRNAs were confirmed by quantitative RT-PCR. MiR-378, a significantly down-regulated miRNA, was selected for further function study. In serum deprived rat H9c2 car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 38 publications
5
91
1
1
Order By: Relevance
“…miR-15 and miR-16 were found to induce apoptosis in chronic lymphocytic leukemia cells by regulating bcl-2 expression (Cimmino et al, 2005). Fang et al showed that miR-378 can inhibit the expression of its target gene caspase-3, thereby reducing ischemic injury in myocardial cells (Fang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…miR-15 and miR-16 were found to induce apoptosis in chronic lymphocytic leukemia cells by regulating bcl-2 expression (Cimmino et al, 2005). Fang et al showed that miR-378 can inhibit the expression of its target gene caspase-3, thereby reducing ischemic injury in myocardial cells (Fang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were routinely cultured in Dulbecco's modified Eagle's medium (DMEM) as previously described with minor modifications (Fang et al, 2012). The medium was changed every 2 d and when confluence was reached, the cells were subcultured by detaching with 0.25% trypsin-EDTA solution and re-seeding into new plates at a ratio of 1:5.…”
Section: Cell Culturementioning
confidence: 99%
“…There is an extensive and growing list of miRNAs regulated by hypoxia, either positively or negatively, in different experimental settings (Kulshreshtha et al, 2008;Loscalzo, 2010;Bussolati et al, 2012;Du et al, 2012;Fang et al, 2012;Guo et al, 2012;Voellenkle et al, 2012). Other miRNAs are hypoxia-independent, but are capable of negatively regulating HIF; these include miR-107, miR-17-92 and miR-519c, whose expression is induced by p53, c-myc and the hepatocyte growth factor (HGF), respectively (Taguchi et al, 2008;Cha et al, 2010;Yamakuchi et al, 2010).…”
Section: Mirnas Participate In Negative and Positive Feedback Loops Tmentioning
confidence: 99%